English and Waray basic stress and intonation patterns a contrastive analysis - Viojan, Epifania R. 1938- (s.n.], 1971)
This is a descriptive-contrastive analysis of the English and Waray stress and intonation systems with the view of arriving at certain results where points of conflicts and points of similarities between the two languages regarding these two features of the language are made known and the learners' errors predicted, and also of providing some means by which the obvious transfer of the native Waray language habits into the speaker's spoken English can be minimized if not totally eliminated.